The downfall of money : Germany's hyperinflation and the destruction of the middle class - Taylor, Fred, 1947- (Bloomsbury Press, 2013)
"A hundred years ago, many theorists believed ... that the world had reached a state of economic perfection, a never-before-seen human interdependence that would lead to universal growth and prosperity. At the time, the German mark was one of the most trusted currencies in the world. Yet the early years of the Weimar Republic in Germany witnessed the most calamitous collapse of a developed economy in modern times. [This book explores] anew the dramatic story of the hyperinflation that saw the mark--worth 4.2 to the dollar in 1914--plunge until it traded at over 4 trillion to 1 by the autumn of 1923"--Dust jacket flap.